Oral squamous cell carcinoma: clinicopathological features from 346 cases from a single Oral Pathology service during an 8-year period - Fabio Ramoa Pires; Amanda Barreto Ramos; Jade Bittencourt Coutinho de Oliveira; Amanda Serra Tavares; Priscilla Silva Ribeiro da Luz; Teresa Cristina Ribeiro Bartholomeu dos Santos (University of São Paulo, 2013)
Epidemiological data from oral squamous cell carcinoma (OSCC) is mostly derived from North American, European and East Asian populations. OBJECTIVE: The aim of this study was to report the demographic and clinicopathological features from OSCC diagnosed in an Oral Pathology service in southeastern Brazil in an 8-year period. MATERIAL AND METHODS: All OSCC diagnosed from 2005 to 2012 were reviewed, including histological analysis of all hematoxylin and eosin stained slides and review of all demographic and clinical information from the laboratory records. RESULTS: A total of 346 OSCC was retrieved and males represented 67% of the sample. Mean age of the patients was 62.3 years-old and females were affected a decade older than males (p<0.001). Mean time of complaint with the tumors was 10 months and site distribution showed that the border of the tongue (37%), alveolar mucosa/gingiva (20%) and floor of mouth/ventral tongue (19%) were the most common affected sites. Mean size of the tumors was 3.4 cm, with no differences for males and females (p=0.091) and males reported both tobacco and alcohol consumption more frequently than females. Histological grade of the tumors revealed that 27%, 40% and 21% of the tumors were, respectively, classified as well-, moderately- and poorly-differentiated OSCC, 26 cases (7.5%) were microinvasive OSCC and 17 cases were OSCC variants. OSCC in males mostly affected the border of tongue, floor of mouth/ventral tongue and alveolar mucosa/gingival, while they were more frequent on the border of tongue, alveolar mucosa/gingival and buccal mucosa/buccal sulcus in females (p=0.004). CONCLUSIONS: The present data reflect the epidemiological characteristics of OSCC diagnosed in a public Oral Pathology laboratory in southeastern Brazil and have highlighted several differences in clinicopathological features when comparing male and female OSCC-affected patients.